1997
DOI: 10.1023/a:1005781320906
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of action of the anti-neoplastic drug lonidamine on drug-sensitive and drug-resistant human breast cancer cells:31 P and 13C nuclear magnetic resonance studies

Abstract: Lonidamine (LND) is a relatively new anti-cancer drug, and several clinical trials have indicated that it may be effective in combinations with other therapeutic modalities. LND is classified within the metabolic inhibitor agents. Multidrug resistance (MDR) phenomenon is often associated with increased energy requirements, and enhanced glycolysis rate. These studies were performed to delineate the mechanism of action of LND on MDR human breast cancer cells, and to investigate whether LND as a single agent, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The infusate, e.g., 13 C-labeled glucose (Glc), is detected together with its metabolic products. In healthy brain metabolism, label of [ 13 C] Glc is incorporated into glutamate (Glu) and glutamine (Gln) via the TCA cycle; in a tumor, non-oxidative glucose consumption leads to 13 Clabeled Lac and alanine (Ala) [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The infusate, e.g., 13 C-labeled glucose (Glc), is detected together with its metabolic products. In healthy brain metabolism, label of [ 13 C] Glc is incorporated into glutamate (Glu) and glutamine (Gln) via the TCA cycle; in a tumor, non-oxidative glucose consumption leads to 13 Clabeled Lac and alanine (Ala) [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…31 P-MRS has been used to demonstrate that transfection of various cancer cell lines with the mdr1 gene, encoding for P-170 (MDR1), results in altered levels of phosphomonoesters (PME) and phosphodiesters (PDE) and an increase in phosphocreatine (PCr) and ATP levels in comparison with wild-type cells [20]. Over the past decade 31 P-, 1 H-and 13 C-MRS studies of a variety of cancer cell lines have revealed further differences in energy and lipid metabolism when comparing drugsensitive parental cells with variants rendered multidrugresistant by selection for drug tolerance [20][21][22][23][24][25][26]. Little is known, however, about the functional significance of the We present here a study of two human RCC lines, established in the Tumor Bank of the German Cancer Research Center, which differ with regard to growth characteristics, degree of differentiation, expression of P-170, and sensitivity to vinblastine (VBL).…”
mentioning
confidence: 99%
“…Treatment of human prostate cancer cells with two differentiating agents, phenylacetate and phenylbutyrate, resulted in an increase of MR detectable lipids and GPC . Perfused cell systems have been used to understand the effects of lonidamine in adriamycin resistant and wild type MCF‐7 cells, tumor necrosis factor‐α treatment of human breast cancer cells, radiation treatment, and cyclophosphamide treatment . Dichloroacetate (DCA), a pyruvate dehydrogenase kinase inhibitor, was used to treat poorly metastatic LNCaP and highly metastatic LNCaP‐LN3 prostate cancer cells.…”
Section: Insights Into Intact Cancer Cell Metabolism Using Cell Perfumentioning
confidence: 99%